Photochemical CO2 Reduction Catalyzed by Trans(Cl)‐[Ru(2, 2′‐bipyridine)(CO)2Cl2] Bearing Two Methyl Groups at 4, 4′‐, 5, 5′‐ or 6, 6′‐Positions in the Ligand. Issue 3 (24th January 2018) - Kuramochi, Yusuke; Itabashi, Jun; Toyama, Mari; Ishida, Hitoshi
Abstract: Photochemical CO2 reduction reactions catalyzed by trans (Cl)‐[Ru(L)(CO)2 Cl2 ] (L=4, 4′‐dimethyl‐2, 2′‐bipyridine (Ru4 dmb ), 5, 5′‐dimethyl‐2, 2′‐bipyridine (Ru5 dmb ) or 6, 6′‐dimethyl‐2, 2′‐bipyridine (Ru6 dmb )) are investigated in N, N ‐dimethylacetamide (DMA)/water (9:1 v/v) containing [Ru(bpy)3 ] 2+ as the photosensitizer and 1‐benzyl‐1, 4‐dihydronicotinamide (BNAH) as the electron donor. The reduction potentials and the density functional theory (DFT) calculations reveal quite similar results for the complexes, however their catalytic efficiencies are significantly different.Ru6 dmb selectively yields CO as the reduction product with lower catalytic rates than the others.Ru4 dmb andRu5 dmb produce both CO and HCOO − at very similar activities when the catalyst concentration is low. However, the catalytic rates forRu5 dmb are higher than those ofRu4 dmb at a higher concentration of the catalysts, where the rate‐determining step is not in the catalytic cycle but in the electron supplying one. The results are discussed in terms of back electron transfer from the catalyst to the photosensitizer or the cage escape yield for the sensitizer–catalyst encounter complex. Abstract : Optimum arrangement : A series of complexes trans (Cl)‐[Ru(bpy)(CO)2 Cl2 ] in which the 2, 2′‐bipyridine ligand was functionalized with two methyl groups was prepared. Photocatalytic CO2 reduction by the complexes in N, N ‐dimethylacetamide/water containing a photosensitizer and an electron donor was examined. The positions of methyl groups in the ligand was found to strongly affect the photocatalytic CO2 reduction.